2010
DOI: 10.1111/j.1755-148x.2010.00720.x
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase I amplification in melanoma is associated with more advanced tumours and poor prognosis

Abstract: SummaryIn this study, we used array-comparative genomic hybridization (aCGH) and fluorescent in situ hybridization (FISH) to examine genetic aberrations in melanoma cell lines and tissues. Array-comparative genomic hybridization revealed that the most frequent genetic changes found in melanoma cell lines were amplifications on chromosomes 7p and 20q, along with disruptions on Chr 9, 10, 11, 12, 22 and Y. Validation of the results using FISH on tissue microarrays (TMAs) identified TOP1 as being amplified in mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…Ingenuity analysis showed that 945 differentially expressed genes are associated with cancer, and 364 differentially expressed genes are associated with dermatological diseases and conditions (Figure S1E). Among the upregulated genes were TOP1 (DNA topoisomerase I), which is associated with advanced melanomas and poor prognosis [28]. Among the downregulated genes were TYRP1 (tyrosinase-related protein 1) and ABCB5 (ATP-binding cassette, sub-family B, member 5), both of which are related to melanoma progression and initiation [29][31].…”
Section: Resultsmentioning
confidence: 99%
“…Ingenuity analysis showed that 945 differentially expressed genes are associated with cancer, and 364 differentially expressed genes are associated with dermatological diseases and conditions (Figure S1E). Among the upregulated genes were TOP1 (DNA topoisomerase I), which is associated with advanced melanomas and poor prognosis [28]. Among the downregulated genes were TYRP1 (tyrosinase-related protein 1) and ABCB5 (ATP-binding cassette, sub-family B, member 5), both of which are related to melanoma progression and initiation [29][31].…”
Section: Resultsmentioning
confidence: 99%
“…Genomic DNA from the Irish cohort was extracted as described previously [10]. Within the Belgian cohort, DNA was extracted using sections from fresh-frozen samples that were incubated overnight at 37°C with DNA lysis buffer (10 mmol/l Tris pH 8.0, 100 mmol/l NaCl, 10 mmol/l EDTA pH 8.0, 10% SDS) and proteinase K. DNA was purified using saline solution (NaCl 5 mol/l) and 100% 2-propanol.…”
Section: Genotypingmentioning
confidence: 99%
“…Within the Irish cohort 2, BRAF mutational analysis was carried out using the ABI Prism TaqMan 7900HT Sequence Detection System (Life Technologies Corporation, Carlsbad, California, USA) in combination with the BRAF V600E single nucleotide polymorphism (SNP) genotyping assay as described earlier [10]. BRAF genotyping was performed on Irish cohort 3 using Sequenom analysis as described above.…”
Section: Genotypingmentioning
confidence: 99%
“…The TOP1 CN gain in CRC has been reported to be in the range of 53–84%, whereas TOP1 /CEN-20 ratios ≥ 1.5 or ≥2.0 were in the range of 30–40% and 10–20%, respectively [14, 18, 19]. Current data suggests that TOP1 CN increases occur predominately in conjunction with the rest of 20q [14, 16, 17, 20] and the CEN-20 region [14, 18]. Therefore the usage of the TOP1 /CEN-20 ratio may underestimate the genuine TOP1 amplifications.…”
Section: Introductionmentioning
confidence: 99%